A heterogeneous data exchange approach for RFID-based logistics-customs clearance public service platform. (20th April 2011) - Deng, Huifang; Li, Han; Li, Su; Yang, Hongji
The heterogeneous data exchange problem of Radio Frequency Identification (RFID) based logistics-customs clearance public service platform is discussed in this paper. By analysing the characteristics of the platform, a heterogeneous data exchange approach is presented, in which a Hybridmatching Algorithm based on Block-Dividing Dynamic Weight (HABDDW) is proposed. The crucial idea of HABDDW is to compare the similarities of the structure and expression between two relation pattern trees. When calculating the similarities, HABDDW not only combines element matching with structure matching, but also integrates linguistic matching with semantic matching. That is, the mapping between any pair of exchanged data is established, and a feasible approach is provided to achieve the goal of information sharing among heterogeneous data.